2020
DOI: 10.26452/ijrps.v11i4.3272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional outcome following ORIF of bimalleolar fractures of the ankle-A prospective study of 30 patients

Abstract: Bimalleolar fractures are common injuries, and stable fracture patterns can be treated conservatively, while complicated, unstable fractures would require surgical intervention. This study aimed to evaluate the functional outcome following ORIF (Open reduction and internal fixation) of these fractures. This was a study of 30 patients with bimalleolar fractures who presented between January 2013 to January 2016 treated with ORIF with a follow-up period of 3 years. Functional outcome was performed with the AOFAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Of all studies, 40 23–61 described their postoperative rehabilitation strategy but did not evaluate effectiveness and 15 20–22,62–73 focused on evaluating the effectiveness of the postoperative rehabilitation strategy. This section reports only those 40 studies that described their postoperative rehabilitation strategy, focusing on weight-bearing, immobilization, and other therapy administered.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of all studies, 40 23–61 described their postoperative rehabilitation strategy but did not evaluate effectiveness and 15 20–22,62–73 focused on evaluating the effectiveness of the postoperative rehabilitation strategy. This section reports only those 40 studies that described their postoperative rehabilitation strategy, focusing on weight-bearing, immobilization, and other therapy administered.…”
Section: Resultsmentioning
confidence: 99%
“…42–47,49–55,58 Other studies advised patients to remain non–weight-bearing for up to 10–12 weeks. 42,50,54,55,57,60 Several studies reported patients being non–weight-bearing until fracture healing was confirmed with radiographic evidence. 49,51,56,57,60…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations